2017
DOI: 10.5194/isprs-archives-xlii-2-w7-863-2017
|View full text |Cite
|
Sign up to set email alerts
|

Standardizing Quality Assessment of Fused Remotely Sensed Images

Abstract: ABSTRACT:The multitude of available operational remote sensing satellites led to the development of many image fusion techniques to provide high spatial, spectral and temporal resolution images. The comparison of different techniques is necessary to obtain an optimized image for the different applications of remote sensing. There are two approaches in assessing image quality: 1. Quantitatively by visual interpretation and 2. Quantitatively using image quality indices. However an objective comparison is difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This is consistent with the results of previous studies [7,12], as well as previous results for the GS and PCA pansharpening methods [23,30,32,36,46,50,51]. It is also consistent with previous results for the mIHS and PCA pansharpening methods [48,52] and the mIHS, GS, and PCA pansharpening methods [53]. However, it is inconsistent with the findings of Sarp, who reported that the PCA method produced better results than the GS pansharpening method for the difference in the correlation coefficient and root mean square error (RMSE) values between the images before and after fusion in both IKONOS and QuickBird in Istanbul [30].…”
Section: Impact Of Pansharpening Methods In Different Regions and Ima...supporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with the results of previous studies [7,12], as well as previous results for the GS and PCA pansharpening methods [23,30,32,36,46,50,51]. It is also consistent with previous results for the mIHS and PCA pansharpening methods [48,52] and the mIHS, GS, and PCA pansharpening methods [53]. However, it is inconsistent with the findings of Sarp, who reported that the PCA method produced better results than the GS pansharpening method for the difference in the correlation coefficient and root mean square error (RMSE) values between the images before and after fusion in both IKONOS and QuickBird in Istanbul [30].…”
Section: Impact Of Pansharpening Methods In Different Regions and Ima...supporting
confidence: 93%
“…These results are consistent with those of Witharana et al, who reported that for GeoEye-1 urban images, the CN method exhibited the highest scores for spatial metrics, followed by the mIHS, GS, and PCA methods, although different spatial metrics, such as the canny edge detection filter, the high-pass correlation coefficient, and the RMSE of a Sobel-filtered edge image, were used [37]. The results are also consistent with previous studies in which the mIHS method achieved better scores for spatial information than the PC method [32,52].…”
Section: Impact Of Pansharpening Methods In Different Regions and Ima...supporting
confidence: 88%
“…Attention should be paid to these factors when statistical indices are used for the quantitative measurement of fusion quality. As some research has pointed out, one direction for future research is a standardized visual quality assessment to objectively compare fusion quality (Pohl et al, 2017). It might be useful to extend such a quality assessment and develop more robust quantitative measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The reference images and fused images were displayed side by side (a double-stimulus (DS) study) to enable the subjects to rank the images produced by the various methods. In a different approach presented in [37], the authors developed a visual quality assessment protocol (VQAP) in which the human evaluator is guided through the process of fused image assessment from global to local features. Criteria such as sharpness, color preservation, and object recognition support the judgment on the quality of the images.…”
Section: Subjective Studymentioning
confidence: 99%